Guidelines for the hydraulic design of a combined fishway-canoe chute at weirs - Heidbreder, Caitlin Jane (Stellenbosch : Stellenbosch University, 2025)
Heidbreder, C. J. 2025. Guidelines for the Hydraulic Design of a Combined Fishway-Canoe Chute at Weirs. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/f8f5b381-2fdd-4bf3-b7ee-6dab4f528e97